1997
DOI: 10.1007/s004420050311
|View full text |Cite
|
Sign up to set email alerts
|

C 4 photosynthesis, atmospheric CO 2 , and climate

Abstract: The objectives of this synthesis are (1) to review the factors that influence the ecological, geographical, and palaeoecological distributions of plants possessing C photosynthesis and (2) to propose a hypothesis/model to explain both the distribution of C plants with respect to temperature and CO and why C photosynthesis is relatively uncommon in dicotyledonous plants (hereafter dicots), especially in comparison with its widespread distribution in monocotyledonous species (hereafter monocots). Our goal is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
889
3
14

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,292 publications
(946 citation statements)
references
References 85 publications
40
889
3
14
Order By: Relevance
“…Edwards and Still (2008) found that the distribution of C4 grasses on Hawaii correlated with areas of lower mean annual precipitation compared to their C3 counterparts. The lower proportion of C4 plants in modern soils within manavai and rock garden soils inferred from δ 13 C values therefore is consistent with higher soil moisture contents in agricultural soils that affect C3/C4 plant ratios (Edwards & Still, 2008; Ehleringer, Cerling, & Helliker, 1997). Historical land use changes, such as extensive sheep farming from ca.…”
Section: Discussionsupporting
confidence: 59%
“…Edwards and Still (2008) found that the distribution of C4 grasses on Hawaii correlated with areas of lower mean annual precipitation compared to their C3 counterparts. The lower proportion of C4 plants in modern soils within manavai and rock garden soils inferred from δ 13 C values therefore is consistent with higher soil moisture contents in agricultural soils that affect C3/C4 plant ratios (Edwards & Still, 2008; Ehleringer, Cerling, & Helliker, 1997). Historical land use changes, such as extensive sheep farming from ca.…”
Section: Discussionsupporting
confidence: 59%
“…There is currently little consensus, however, regarding physiological constraints on C 4 plant distribution in cold climates. Dissociation of the C 4 enzymes pyruvatephosphate dikinase and PEP carboxylase (Long, 1983;Potvin et al, 1986), Rubisco limitation (Long 1999;Kubien et al, 2003), and lower quantum yield of C 4 versus C 3 grasses (Ehleringer et al, 1997) at lower temperatures have all been proposed as explanations for the scarcity of C 4 species in cold environments. Most of these studies have focused on low temperatures during the growing season, but our results suggest that winter temperatures may be equally important in limiting C 4 grasses.…”
Section: Late Pleistocene Climatementioning
confidence: 99%
“…However, this low temperature limit may have been altered during the late Pleistocene due to shifts in dominance between C 3 and C 4 species. The higher quantum yield of C 3 species at low temperatures may limit C 4 grass distribution at sites with cooler growing season temperatures via competitive exclusion (Ehleringer et al, 1997). During the late Pleistocene, however, C 4 photosynthesis may have been favored at lower summer temperatures when reduced crossover temperatures (the mean monthly temperature at which C 4 plants have a higher quantum yield than C 3 plants) resulted from decreased atmospheric CO 2 concentration (Ehleringer et al, 1997;Koch et al, 2004).…”
Section: Late Pleistocene Climatementioning
confidence: 99%
“…C 4 plants, in contrast to C 3 plants, are reported to be better adapted to water stress [10,11] due to its (i) distinctive leaf anatomy (Kranz anatomy) (ii) having two carboxylation pathways (phosphoenolpyruvate carboxylase (PEPC) and RUBISCO) in mesophyll and bundle sheats that limit photorespiration and increase carboxylation efficiency [12] and (iii) requiring a lower CO 2 saturation point for photosynthesis than C 3 plants [13].…”
Section: Introductionmentioning
confidence: 99%